Marker-assisted selection strategy to pyramid two or more QTLs for quantitative trait-grain yield under drought - Kumar, Arvind; Sandhu, Nitika; Dixit, Shalabh; Yadav, Shailesh; Swamy, B. P. M.; Shamsudin, Noraziyah Abd Aziz (Springer, 2018)
Marker-assisted breeding will move forward from introgressing single/multiple genes governing a single trait to multiple genes governing multiple traits to combat emerging biotic and abiotic stresses related to climate change and to enhance rice productivity. MAS will need to address concerns about the population size needed to introgress together more than two genes/QTLs. In the present study, grain yield and genotypic data from different generations (F3 to F8) for five marker-assisted breeding programs were analyzed to understand the effectiveness of synergistic effect of phenotyping and genotyping in early generations on selection of better progenies Based on class analysis of the QTL combinations, the identified superior QTL classes in F3/BC1F3/BC2F3 generations with positive QTL x QTL and QTL x background interactions that were captured through phenotyping maintained its superiority in yield under non-stress (NS) and reproductive-stage drought stress (RS) across advanced generations in all five studies. The marker-assisted selection breeding strategy combining both genotyping and phenotyping in early generation significantly reduced the number of genotypes to be carried forward. The strategy presented in this study providing genotyping and phenotyping cost savings of 25–68% compared with the traditional marker-assisted selection approach. The QTL classes, Sub1 + qDTY 1.1 + qDTY 2.1 + qDTY 3.1 and Sub1 + qDTY 2.1 + qDTY 3.1 in Swarna-Sub1, Sub1 + qDTY 1.1 + qDTY 1.2 , Sub1 + qDTY 1.1 + qDTY 2.2 and Sub1 + qDTY 2.2 + qDTY 12.1 in IR64-Sub1, qDTY 2.2 + qDTY 4.1 in Samba Mahsuri, Sub1 + qDTY 3.1 + qDTY 6.1 + qDTY 6.2 and Sub1 + qDTY 6.1 + qDTY 6.2 in TDK1-Sub1 and qDTY 12.1 + qDTY 3.1 and qDTY 2.2 + qDTY 3.1 in MR219 had shown better and consistent performance under NS and RS across generations over other QTL classes Deployment of this procedure will save time and resources and will allow breeders to focus and advance only germplasm with high probability of improved performance. The identification of superior QTL classes and capture of positive QTL x QTL and QTL x background interactions in early generation and their consistent performance in subsequent generations across five backgrounds supports the efficacy of a combined MAS breeding strategy.